Beyond myeloid neoplasms germline guidelines: Validation of the thresholds criteria in the search of germline predisposition variants - Mestre, Julia; Chaparro, Lorea; Manzanares, Ana; Xicoy, Blanca; Zamora, Lurdes; Sole, Francesc; Calvete, Oriol (EJHaem, 2024)
Introduction Germline predisposition to myeloid neoplasms can be suspected in patients younger than 50 years or when harboring mutations with a variant allele frequency (VAF) higher than 30% for point mutations in specific genes. To investigate the VAF thresholds’ accuracy we have explored the prevalence of germline variants below the 30% VAF threshold. Methods A total of 40 variants with VAF lower than 30% in bone marrow samples of myeloid neoplasm patients were selected and studied in CD3+ cells. Results All the selected variants were not found in CD3+ cells except one variant in the SF3B1 gene. However, the whole series was found somatic. Selected variants were also evaluated with our previously studied series of 52 variants with VAF higher than 30%. Conclusion Our study suggests that variants with VAF below 30% are strong somatic candidates but the variants with VAF higher than 30% cannot be considered of germline origin.